Factores que contribuyeron o limitaron el desarrollo del proyecto mujeres Acompañando Mujeres en el distrito de Virú, Región La Libertad, 2022 - Gutierrez Laiza, Ingrid Liliana (2024)
The objective of this study is to describe and analyze the factors that have contributed to and limited the development of the Basic Accompaniment service within the Women Accompanying Women Community Strategy of the National Program AURORA during the 2021 – 2022 pandemic, in the district of Virú, La Libertad region. The conducted research is qualitative, employing a case study approach, using a significant sample selected on judgement and convenience. The study information was gathered from 11 mentors, 4 users, and 1 AURORA program mentor coordinator, and through documentary review sources. The research findings reveal that the analyzed community strategy promotes citizen participation –social capital– through the co-management of social actors – specifically, mentors – who promote a transformative approach in combating violence against women. These volunteer women, who have experienced the impacts of discrimination and sexism in their local context, emerge as social actors of their own change and that of their surroundings, creating networks of emotional support, known as sisterhood. This service includes a discourse of social change, facilitated by volunteers who come together for a common social purpose: preventing and combatting violence against women who have suffered from this social issue, through accompaniment during a year of intervention, aiming to transform the attitudes of these women, reinforcing their socio-emotional skills. The limitations in enhancing the operational processes of the basic accompaniment service were the low participation of volunteers in monitoring and evaluating the service, and the insufficient working hours of the services of the Women's Emergency Center (CEM VIRÚ). However, despite these challenges, significant positive changes in the attitudes of the women who received this service were accomplished.